The Musical Identity, Women's Struggles, and Ecological Knowledge in the Samanim’s Oral Opera - Septina Rosalina Layan; Darlane Litaay; Veronika Kanem; Theodora M. Pahun (Institut Seni Indonesia Yogyakarta, 2025)
Samanim’s oral opera is a programmatic musical composition designed to embody the cultural identity of Malind, highlighting the challenges faced by women and the rich local ecological knowledge, all conveyed through the medium of performing arts. This research seeks to uncover, express, and revitalize Malind local wisdom, often marginalized in dominant narratives of development and modernity. In this context, Samanim’s oral opera serves as a form of artistic expression and a vital tool for challenging established knowledge systems, all while elevating Indigenous perspectives in the broader discussion. Rooted in the principles of decoloniality, local feminism, and Indigenous ecology, this work emphasizes the vital role of women as key participants and guardians of values, knowledge, and the continuity of traditions across generations. This study utilizes practice-led research, a method selected for its ability to foster knowledge creation through creative practice, which in turn provides valuable insights via aesthetic experiences and thoughtful artistic processes. This analysis delves into three important areas: the musical and cultural identity of the Malind people, the vital roles women play in preserving and sharing knowledge, and the ecological values represented by Samanim as a central figure. The findings show that the Samanim’s oral opera plays a vital role in shaping the collective memory of the Malind community by how it engages with musical elements, cultural narratives, and representations of women. This work highlights the vital contributions of women in both cultural and ecological stewardship, while addressing pressing contemporary challenges like environmental degradation, social marginalization, and the impact of capitalism on Indigenous ways of life. In the end, Samanim’s oral opera operates as a medium through which cultural values and political reflection, showcasing how art can inspire resistance, enhance critical awareness, and contribute to sustainable thinking.